Detection of Chlamydia trachomatis by the polymerase chain reaction in swabs and urine from men with non-gonococcal urethritis. - Palmer, H M (1991)
A polymerase chain reaction (PCR) was developed for Chlamydia trachomatis in which a 380 base pair DNA fragment was amplified. Amplification occurred with the DNA from the 15 serovars but not with that from other Chlamydia spp or with DNA from a variety of other organisms. Chlamydial DNA (10(-16) g) could be detected and the PCR seemed to be able to detect single organisms. Urethral swabs were obtained from 37 men with acute non-gonococcal urethritis (NGU), 18 (49%) of whom were positive for C trachomatis by MicroTrak. As a result of clinical re-examinations 65 urethral swabs were available for analysis by the PCR. In comparison with MicroTrak, PCR had a sensitivity of 95%, a specificity of 94%, a positive predictive value of 86% and a negative predictive value of 98%. The PCR was apparently less sensitive (82%) in tests on urine samples. Overall, however, values of sensitivity and specificity of the PCR compared favourably with those of MicroTrak. The PCR for C trachomatis is likely to be a valuable technique for research, but problems of DNA contamination suggest that it should not be recommended for routine diagnosis.